The Model of Hāmil al-Qur’ān Development in Pesantren: The Integration of Lafẓan, Ma’nan, and ‘Amalan - Daud Daud; Asriana Kibtiyah; Silmi Adawiya (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyse the role of Madrasatul Qur’an Islamic Boarding School Tebuireng, Jombang, in shaping hāmil al-Qur’ān individuals through three main dimensions: lafẓan (memorisation), ma’nan (understanding), and ‘amalan (practice). This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, participatory observation, and documentation and analysed using Miles and Huberman's interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings reveal that the pesantren plays a significant role in developing hāmil al-Qur’ān students in an integrative manner. The lafẓan dimension is implemented through structured tahfiz learning based on talaqqi, memorisation, submission, and repetition (muroja’ah), with an emphasis on accurate recitation according to tajwid rules. The ma’nan dimension is developed through tafsir studies, ulūmul Qur’an, and Arabic language reinforcement, enabling students to understand Qur’anic meanings contextually. Meanwhile, the ‘amalan dimension is internalised through habituation of worship, role modeling, and pesantren culture, which shape Qur’anic character. The novelty of this study lies in the construction of an integrative hāmil al-Qur’ān development model that connects memorisation, understanding, and practice within a holistic and sustainable educational system.